Treating Speech Anxiety in Youth: A Randomized Controlled Microtrial Testing the Efficacy of Exposure Only Versus Exposure Combined With Anxiety Management Strategies. Issue 6 (November 2021) - de Jong, Rachel; Lommen, Miriam J.J.; Timmerman, Marieke E.; van Hout, Wiljo J.P.J.; Kuijpers, Rowella C.W.M.; de Jong, Peter J.; Nauta, Maaike H.
Highlights: A short CBT training of five sessions was effective in treating speech anxiety in youth. Exposure only training was not more effective than exposure combined with AMS. CBT components did not seem to affect thoughts, feelings, and actions differentially. Abstract: CBT for anxious youth usually combines anxiety management strategies (AMS) with exposure, with exposure assumed to be critical for treatment success. To limit therapy time while retaining effectiveness, one might optimize CBT by restricting treatment to necessary components. This study tested whether devoting all sessions to exposure is more effective in reducing speech anxiety in youth than devoting half to AMS including cognitive or relaxation strategies and half to exposure. After a 6-week waitlist period, adolescents with speech anxiety (N  =  65; age 12–15; 42 girls) were randomized to a 5-session in-school group-based CBT training consisting of either (1) exposure-only (EXP+EXP) or (2) cognitive strategies followed by exposure (COG+EXP) or (3) relaxation strategies followed by exposure (REL+EXP). Clinical interviews, speech tests, and self-report measures were assessed at pretest, posttest, and follow-up. For all conditions (a) the intervention period resulted in a stronger decline of speech anxiety than waitlist period; (b) there was a large sized reduction of speech anxiety that was maintained at six-week follow-up; (c) there was no meaningful difference in the efficacy of EXP+EXP versus COG+EXP or REL+EXP. These findings suggest that devoting all sessions to exposure is not more effective than combining exposure with AMS. AMS appeared neither necessary for CBT to be effective, nor necessary for youth to tolerate exposure. This indicates that CBT can be optimized by restricting treatment to exposure.